Awareness and understanding of government total asset management implementation strategy - Musa, Mohd. Roszaimy (2015)
Management of government assets have been dealing with various vulnerabilities as stated in the Auditor General's Report. It seems that, there is a gap of understanding and awareness amongst government employees regarding on the spirit of Government Asset Management Policy and the operation of their daily work as managers and guardians for government assets. The aim of this study is to examine the relationship of understanding and awareness of employees towards four strategic implementation elements that withdrawn from policy document known as governance, process, technology and human in their routine at work. Mixed mode research was designed to explore the current practice, which is focusing on the management of government movable assets. Content analysis was performed on eight working procedures to identify whether there is a presence of the elements in those documents, and it revealed that all elements were discovered. A questionnaire survey was design from this output to test the level of understanding and awareness of employees. Descriptive analysis of data collected from 239 respondents in Asset Management Unit of Federal Ministries and Departments demonstrated that, the level of understanding and awareness amongst respondents towards strategic implementation elements was good. However, total awareness level has a lower mean score than the understanding level. Therefore, correlation and regression analysis was conducted to find the relationship between understanding the elements and employees’ level of awareness, which has resulted with significant correlations between those variables. In fact, understanding the element of process was the highest contribution to increase asset personnel awareness on their routine of work followed by understanding the element of governance, while the element of technology and human has no contribution towards it. It is recommended to further this study on different asset management context and its population